COMPARISON PERFORMANCE NON-HIERARCHICAL CLUSTER: Case Study: Central Java Regional Competitiveness Index - Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Dyah Purwanti; Sigit Budiantono (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2023)
The Regional Competitiveness Index (RCI) is a benchmark for measuring a region's ability to compete in a market. RCI covers several indicators, including infrastructure, human resource quality, innovation, and government policies supporting economic growth. This study aims to test the performance of several non-hierarchical cluster techniques. The data used Regional Competitiveness Index data in 35 Cities in Central Java in 2022 from the National Research and Innovation Agency (BRIN). The optimal number of clusters recommended using the Elbow method technique is as many as 3. The K-Means method is the best considering the largest Silouhette and R2 values and the smallest AIC/BIC. Cluster 1 has negative values for Pillars 2, 4, 9, and 10. Members in this cluster are Sukoharjo, Magelang City, Surakarta, Salatiga, Pekalongan City, and Tegal City. On the other hand, Cluster 2 has only one negative value for pillar nine. The members of this cluster are Semarang City. The third cluster is only positive in pillar nine and pillar 28. The members of this cluster are as many as 28 other districts. A comprehensive and targeted policy is needed so that the competitiveness index of the Central Java region continues to increase